LA RICCA LEGISLAZIONE CANONICA DEL SINODO PROVINCIALE I (1872) E LA POSIZIONE DELLA SEDE APOSTOLICA CIRCA GLI ATTI SINODALI - ARIEŞAN, Ilie (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2016)
The Ample Canonic Legislation of the 1st Provincial Synod (1872) and the Position of the Holy See Regarding the Acts of the Synod. The current paper aims to emphasize the role of the 1st Provincial Synod as a fundamental juridical apparatus for the particular law of our Church and as a fons iuris for Codex Canonum Ecclesiarum Orientalium. We know that our ius particulare Ecclesiae sui iuris is in the process of being drawn up. This paper focuses on the rich canonic analysis of the 1st Provincial Synod (1872) and on the position of the Apostolic See regarding the acts of this synod which was the most important one amongst the other two Romanian provincial synods approved by the Holy See, because it was meant to renew the Romanian canonic legislation and to replace the famous collection Directorum Legis, also known as Pravila (1652), in use since before the Union and presented as a fons iuris even in the norms of the synods ulterior to the Union with Rome. An important role in our approach is given to the analysis of several aspects characteristic to the 1st Provincial Synod such as, for example, the Sacri canones as a fons iuris of a great importance for the 1st Provincial Synod, since it made the Romanian Church a unique one among the other Oriental Churches United with Rome through its fidelity towards the Oriental tradition and patrimony. For a better understanding of the Synod, we analyzed also the Ad decreta Synodalia animadversiones (cf. Mansi 42), which revealed the importance of the Romanian synod obvious even in a comparison with the synods of the other Catholic Oriental Churches from the same period in the Habsburg Empire, precisely because it was the intention of the Holy See of Rome to present the 1st Provincial Synod as a model for them. The foundation of the new ecclesiastic province of Alba Iulia and Făgăraş (Ecclesiam Christi Bulla of Pope Pius IX, from Nov. 26th 1853) was of a fundamental importance for the Romanian Church and for its legislation. It was a great need for the exact knowledge of the spirit of the clergy and of the faithful, of their state, of their customs and of all that could have referred to the preservation in this province of the purity of faith and of the holiness of the rites and discipline. All these aspects reflected in the concern of Rome were expressed initially by the Apostolic Nuncio from Vienna, who asked the metropolitan and his sufraganeous bishops for a complete informative report regarding various disciplinary aspects from their own bishoprics, information about the provincial and local synods, about the married clergy, the ecclesiastical courts, the Sacrament of Marriage, the diriment impediments etc., with the purpose of checking up if the customs of each bishopric were conform with the oriental canonic law and if any remaining stains from the time of the Schism could still be found in the rite and the discipline of this Church. One can notice that the Romanian Greek-Catholic Church had its own problems, among which the reports revealed, besides important aspects of sacramental law, the issue of synodality, the one of the rights of the archpriests, the issue of the organization of a new ecclesiastical province, the one referring to the communicatio in sacris, to the election of the metropolitan and of the bishops, the one concerning the role of the laity in the church. Several of these issues caused Rome true difficulties. A famous example is offered by the matrimonial practice preceding the Union, supported vividly by the Romanian metropolitan A.Ş. Şuluţiu, who allowed the archpriests to function as a first instance court. In the Romanian Greek-Catholic Church, the ius particulare has as its fundamental juridical apparatus especially the three Provincial Synods of 1872, 1882 and 1900. The knowledge of this legislation is fundamental to the canonic direction and drawing up of the ius particulare Ecclesiae sui iuris. REZUMAT: Ampla legislaţie canonică a Sinodului provincial I (1872) şi poziţia Sfântului Scaun referitoare la actele sinodale. Prezentul articol îşi propune să scoată în relief Sinodul provincial I ca aparat juridic fundamental pentru dreptul particular al Bisericii noastre şi ca fons iuris pentru Codex Canonum Ecclesiarum Orientalium. În prezent ius particulare Ecclesiae sui iuris este în plin proces de redactare. Acest studiu analizează bogata legislaţie canonică a Sinodului provincial I (1872) şi poziţia Scaunului Apostolic faţă de actele Sinodului, care a fost cel mai important dintre cele trei Sinoade provinciale româneşti aprobate de Scaunul Apostolic, pentru faptul că era menit să reînnoiască legislaţia canonică românească şi să se substituie faimoasei Colecţii Directorium legis, cunoscută şi sub numele de Pravila (1652), în vigoare înainte de Unire, şi prezentă ca fons iuris chiar şi în normativa unor Sinoade ulterioare Unirii cu Roma. Un rol însemnat în abordarea acestui subiect este acordat analizei câtorva aspecte caracteristice Sinodului provincial I cum ar fi, de exemplu, Sacri canones în calitatea lor de fons iuris de mare importanţă în cadrul Sinodului provincial I deoarece acest fapt evidenţiază Biserica română ca fiind unică între celelalte Biserici orientale Unite cu Roma, prin fidelitatea ei faţă de tradiţia şi patrimoniul oriental. Pentru o mai bună înţelegere a Sinodului, s-a analizat şi Ad decreta Synodalia animadversiones (cf. Mansi 42), care scoate în relief importanţa acestuia chiar şi comparativ cu sinoadele celorlalte Biserici orientale din Imperiul Habsburgic din aceeaşi perioadă, tocmai pentru că în intenţia Scaunului Apostolic de la Roma, Sinodul provincial I era menit să servească drept model acestora. De o importanţă fundamentală pentru Biserica română şi pentru legislaţia ei a fost întemeierea noii provincii ecleziastice de Alba-Iulia şi Făgăraş (Bulla Papei Pius al IX-lea Ecclesiam Christi, din 26 nov. 1853), deoarece se impunea necesitatea cunoaşterii cu exactitate a spiritului clerului şi credincioşilor, a condiţiei lor, a obiceiurilor şi a tot ceea ce ar fi putut să facă referire la păstrarea în această provincie a purităţii credinţei şi a sfinţeniei riturilor şi disciplinei. În această direcţie s-au şi îndreptat preocupările Scaunului Apostolic de la Roma, mai întâi prin intermediul Nunţiului Apostolic din Viena, prin care s-a cerut mitropolitului şi episcopilor sufragani, care făcuseră în scris, cu titlu informativ, un raport complet cu privire la diferite puncte disciplinare din propriile eparhii, informaţii despre sinoadele provinciale şi eparhiale, despre căsătoria clericilor, despre tribunalele bisericeşti, despre sacramentul căsătoriei, despre impedimentele dirimante etc., cu scopul de a se verifica dacă obiceiurile din respectivele eparhii erau conforme cu dreptul canonic oriental şi dacă nu cumva s-au strecurat în ritul şi disciplina acestei Biserici vreuna din erorile dobândite în perioada schismei. După cum putem să ne dăm seama, nici în Biserica greco-catolică română nu lipseau problemele. Între acestea sunt amintite, în afară de aspectele importante de drept sacramental, problema sinodalităţii, apoi cea a drepturilor protopopeşti, problema organizării noii provincii bisericeşti, aceea referitoare la communicatio in sacris, a alegerii mitropolitului şi a episcopilor, aceea a rolului laicilor în Biserică. Câteva din aceste probleme au provocat Scaunului Apostolic de la Roma adevărate dificultăţi. Un exemplu faimos, în acest sens, este cel al practicii matrimoniale de dinaintea Unirii, susţinută cu insistenţă de Mitropolitul român A.Ş. Şuluţiu, care acorda protopopilor facultatea de a funcţiona ca tribunale de primă instanţă. În Biserica greco-catolică română ius particulare Ecclesiae sui iuris are ca aparat juridic de bază îndeosebi cele trei sinoade provinciale de Alba-Iulia şi Făgăraş (1872, 1882, 1900), de aceea, cunoaşterea unei asemenea legislaţii este fundamentală orientării canonice şi redactării acestuia. Cuvinte cheie: legislaţia canonică; dreptul particular; greco-catolic; aparatul juridic; Sinodul Provincial I (1872).